To Live, Not Only Survive—An Ongoing Endeavor: Resilience of Adult Swedish Women Abused as Children - Gunnarsdóttir, Hrafnhildur; Löve, Jesper; Hensing, Gunnel; Källström, Åsa (Frontiers in Public Health, 2021)
Background: A significant proportion of individuals exposed to maltreatment in childhood adapt positively in adulthood despite the adversities, i.e., show resilience. Little is known about resources and processes related to adulthood that promote resilience. Since women are overrepresented as victims of intrafamilial violence, understanding resilience among adult women is important. Objective: To explore experiences of resilience among adult women who perceive well-being and well-functioning although being exposed to maltreatment during childhood. Participants and Setting: This study included 22 women with experiences of childhood maltreatment, mean age of 48 years, living in Sweden. Methods: Individual interviews were conducted and analyzed according to constructivist grounded theory. Results: The process of resilience was experienced as an ongoing endeavor to live, not only survive, an internal process that interacted with external processes involving social relations and conditions. This endeavor was built on four interrelated resources: establishing and maintaining command of life; employing personal resources; surrounding oneself with valuable people; and reaching acceptance. These worked together, not in a linear or chronological order, but in up and down ways, turns and straight lines (now and then), through the process from maltreatment to well-being. Conclusion: Resilience was found to rest on intrapersonal and interpersonal resources. Individual's inherent capabilities can be, depending on life circumstances and available resources, realized in a way that promote well-being and well-functioning despite severe adversities. Therefore, public health initiatives, social services, and policies should provide conditions that help women maltreated in childhood to live fully rather than merely to survive.